Counter-terrorism & the intelligence network in Europe - Cross, M. K. D. (International journal of law, crime and justice, 2023)
The European intelligence space is reaching a new level of maturity because of an increasingly consolidated transgovernmental network of intelligence professionals. What explains the change in this key security network, especially given the challenges inherent in intelligence sharing? The overall strengthening of the European transgovernmental intelligence network is a product of both informal, bottom-up networking and formal, top-down policies to enhance intelligence sharing. Yet, it is clear that the informal side is of utmost importance given the difficulties inherent in trusting outsiders with valuable information. It is through informality that the transgovernmental network shares best practices and knowhow, strengthening the backbone of the European intelligence space. At the same time, there is a realm of intelligence sharing that is still subject to deep secrecy, the dynamics of which are very difficult to truly know. As a result, there is a disjuncture between expert-level intelligence sharing and community governance practices.